Metacognitive Strategy Observation in Teaching Reading Skills the Teachers in Primary School - Alap, Pati; Mahamod, Zamri (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to explore the teaching of metacognitive strategies in reading skills in primary school Malay conducted a case study on the teaching of primary teachers in the state. This study combines the concepts and principles of the Theory of Constructivism, Teaching Metacognition and Theory of Cooperative Teaching reading skills in teaching Malay language. Study participants consisted of eight teachers Malay. The selection of the study participants was selected for sampling purposes. Data collection was done through structured semi-structured interviews, classroom teaching observations, document analysis and researcher field notes. Data were analyzed using ATLAS.ti version 8 software, descriptive and presented in narrative form. The findings show that metacognitive strategies in teaching reading skills involve group learning, reinforcing experiences and achievement of goals